Dimensionamento, construção e realização de testes de desempenho de um tubo de vórtice que opere em baixas pressões para acionamento por energia solar - Silva, George Miranda Alves de Moraes e (2012)
This paper aims to scale, build and test a new vortex tube, operating from the use of compressed air at pressures below the pressure ranges typical of this unconventional cooling device for the purpose of obtaining drafts cold for air conditioning. For that were originally studied theoretical and experimental aspects of flow processes through tests performed in the laboratory with a commercial vortex tube. Known influence of geometric parameters (such as the ratio between the length and internal diameter of the tube and the diameter of the diaphragm hole) and the thermophysical properties (such as inlet pressure gauge in the compressed air tube and the mass flow rate of the stream cold) air in the performance of the vortex tube, gave up the step of sizing the same. After engineered and designed parts of the tube, the final steps were the manufacture of pipe and conducting experimental tests, beyond the selection of a photovoltaic array to provide the power required to drive the compressor. The results of the laboratory tests with a vortex tube counter-current type, internal diameter D equal to 16.5 mm and a length equal to fifteen times this value, and configured diaphragm orifice diameter of 0.5D showed that temperatures of the cold air flow of 9.5 °C at a mass flow of 40% of the mass flow input are obtained when delivered by the compressor inlet gauge pressure of 3 bar and volumetric flow rate of 3.15 L/s compressed air.